2014
DOI: 10.1007/s40195-014-0154-z
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Nano-Sized Particle-Reinforced Metal Matrix Composites: A Review

Abstract: Compared to the micro-sized particle-reinforced metal matrix composites, the nano-sized particle-reinforced metal matrix composites possess superior strength, ductility, and wear resistance, and they also exhibit good elevated temperature properties. Therefore, the nano-sized particle-reinforced metal matrix composites are the new potential material which could be applied in many industry fields. At present, the nano-sized particle-reinforced metal matrix composites could be manufactured by many methods. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…Notably, a remarkable shortcoming, that is, the agglomeration of particle reinforcements which is characterized by the clustered regions distributing around the grain or phase boundaries, has constrained the optimal coupling of strength and plasticity of Al alloy matrix composites. In the past few years, direct melting reaction (DMR) which is a typical in situ processing method has been devoted to modify the distribution of particles in matrix and to suppress the agglomerations [5][6][7]. Nevertheless, the agglomeration of particles is still a challenge [8].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a remarkable shortcoming, that is, the agglomeration of particle reinforcements which is characterized by the clustered regions distributing around the grain or phase boundaries, has constrained the optimal coupling of strength and plasticity of Al alloy matrix composites. In the past few years, direct melting reaction (DMR) which is a typical in situ processing method has been devoted to modify the distribution of particles in matrix and to suppress the agglomerations [5][6][7]. Nevertheless, the agglomeration of particles is still a challenge [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reinforced nanoparticles tend to be clustered and agglomerated in the matrix due to their high specific surface energy. These cluster and agglomeration of the nanocomposites in the matrix would decrease the mechanical performance of the nanocomposite [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that decreasing the particle sizes improves the mechanical properties of metal matrix composites (MMCs) [6]. It is found that nano-sized reinforcements enhance the mechanical properties more effectively than the micron-sized ones [7]. A variety of techniques for fabricating nano-composites are developed, such as high energy milling [8], ball milling [9] and nano-sintering [10].…”
Section: Introductionmentioning
confidence: 99%